'On Earth as it is in Heaven': A Critical Discussion of the Theology of Bill Johnson. Issue 2 (October 2015) - Shuttleworth, Abigail D.
<x content-type="archive" xml:space="preserve">Abstract</x> This article discusses the theology espoused by Bill Johnson, the senior pastor of Bethel Church in Redding, California. Johnson was an Assemblies of God pastor until 2006 when Bethel Church chose to withdraw from affiliating with the Assemblies of God USA. Johnson is influenced by this traditional Pentecostalism as well as the Third Wave Charismatic leader John Wimber. Johnson's theology is framed by the 'on earth as it is in heaven' motif drawn from Matthew 6:10. This article specifically addresses the Christological, soteriological and eschatological emphases of Bill Johnson's theology.